Molecular Detection of Helicobacter pylori by Real Time- PCR in Dyspeptic Patients - B .Salih , Manal; M. Kadhim, Baidaa; S. Abdulhussein, Haider (University of Thi-Qar Journal of Science, 2019)
Helicobacter pylori is one of the most common infection worldwide and is associated with gastric disorders. H. pylori is genetically unstable and this reflected on its virulence factors and type of diseases. Cytotoxin associated gene A (CagA) product is a major virulence factor is thought to be associated with gastric diseases. In the present study, we used RT-PCR for rapid detection of H. pylori infection in peptic ulcer patient, the determination of CagA gene directly from gastric biopsy specimens and determining relationship between gastric cancer and H. pylori. Gastric biopsy were collected from 54 patients with disorders in digestive system from AL-Hussein teaching hospital. The results of current study showed that the presence of 16SrRNA for H. pylori was 21(38.9%), 15 of 24(62.5%) were males and 6 of 30(20.0%) were females, whereas the percentage of CagA gene was 18(33.3%), 12 of 24 (50%) were males and 6 of 30 (20%) were females by using Real time quantitative PCR in 54 biopsy specimens. These result revealed a significant difference between males and females. Our study indicated that CagA gene RT-PCR is the most specific for the detection of H. pylori in gastric biopsy specimens in patients with gastric cancer compared with 16SrRNA gene . There were significant differences (p≤0.05) in CagA positive rate, among different diseases. In this study the presence of H. pylori in patients with Gastric cancer and peptic ulcer has been demonstrated by using RT-PCR method to support the hypothesis that H. pylori has a place in etiology of gastric cancer.